Impact of Solid Waste Management on Land Pollution in Northern Division Mbale City - Jovia Joan Namutosi (Uganda Christian University, 2024)
This study was about the impact of solid waste management on Land pollution in Northern Division, Mbale City. The study was guided by the following objectives; to determine the factors responsible for poor solid waste management in Northern Division, Mbale City.to evaluate the effects of existing waste management methods on Land pollution in Northern Division, Mbale City.to establish strategies for the better management of solid waste in Northern Division, Mbale City. The study used a descriptive research design. The target sample size was 100 which comprised of commercial community i.e. traders, like shops owners, market vendors, household heads, health inspectors, local leaders like councilors, a private refuse collector and council engineer. 100 questionnaires were issued out of which 75 responses were received, translating into 75% response rate and 30 respondents were interviewed and only 20 accepted using self-administered questionnaires for both quantitative and qualitative methods and interview checklist. This chapter presents findings the impact of solid waste management on Land pollution in Northern Division. The respondents were asked to indicate their Age, Sex, Highest academic qualification and marital status, the research instruments used for data collection were relevant as they analyzed the data and ensured reliability and validity of the findings got from the study area, the study focused on the impact of solid waste management on Land pollution in Northern Division, Mbale City. The conclusion of this study was in reference to the discussion of research findings under the three dimensions of job design, working conditions, and organisation culture. The study concluded that Effective solid waste management is crucial for maintaining environmental health, reducing land pollution, and improving the quality of life in urban areas. In the Northern Division of Mbale City, addressing the challenges of poor waste management requires a multi-faceted approach. Implementing comprehensive strategies can significantly enhance waste management practices, minimize environmental impact, and foster sustainable development.